Gold Aerogels: Three-Dimensional Assembly of Nanoparticles and Their Use as Electrocatalytic Interfaces - Wen, Dan; Liu, Wei; Haubold, Danny; Zhu, Chengzhou; Oschatz, Martin; Holzschuh, Matthias; Wolf, Andre; Simon, Frank; Kaskel, Stefan; Eychmueller, Alexander (ACS nano, 2016)
Three-dimensional (3D) porous metal nanostructures have been a long sought-after class of materials due to their collective properties and widespread applications. In this study, we report on a facile and versatile strategy for the formation of Au hydrogel networks involving the dopamine-induced 3D assembly of Au nanoparticles. Following supercritical drying, the resulting Au aerogels exhibit high surface areas and porosity. They are all composed of porous nanowire networks reflecting in their diameters those of the original particles (5-6 nm) via electron microscopy. Furthermore, electrocatalytic tests were carried out in the oxidation of some small molecules with Au aerogels tailored by different functional groups. The beta-cyclodextrin-modified Au aerogel, with a host-guest effect, represents a unique class of porous metal materials of considerable interest and promising applications for electrocatalysis.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Au aerogels; dopamine; electrocatalysis; host-guest interaction; nanoparticle assembly; porous metal